Pretty guardian Sailor Moon eternal edition. Volume 2 - Takeuchi, Naoko (Kodansha Comics, an imprint of Kodansha USA Publishing LLC, 2018)
Teenager Usagi is not the best athlete, she's never gotten good grades, and, well, she's a bit of a crybaby. But when she meets a talking cat, she begins a journey that will teach her she has a well of great strength just beneath the surface and the heart to inspire and stand up for her friends as Sailor Moon!